Modafinil Induces Wakefulness Without Intensifying Motor Activity or Subsequent Rebound Hypersomnolence in the Rat - Edgar, Dale M.; Seidel, Wesley F. (The Journal of pharmacology and experimental therapeutics, 1997)
Modafinil, a novel compound for treating excessive sleepiness, potently increases wakefulness in laboratory rodents, cats, monkeys and humans. Although its mechanism of action is unknown, modafinil appears to be unlike classic stimulants. We investigated this generality by testing the selectivity of this compound for wake-promoting effects ( e.g., relative to locomotor effects) and homeostatic sleep responses after drug-induced waking relative to the prototypical stimulant methamphetamine (METH). Continuous measures of electroencephalogram (EEG) sleep-wakefulness, locomotor activity (LMA) and body temperature (Tb) were obtained from adult male Wistar rats 3 days before and after treatment with modafinil (30, 100 and 300 mg/kg i.p.), 0.25% methylcellulose (vehicle) or METH (0.5 and 1.0 mg/kg i.p.). Individually housed rats in a 24-h light-dark cycle (LD 12:12) were treated 5 h after lights-on (CT-5). LMA and Tb were monitored via intraperitoneal telemetry. Sleep-wake stages and LMA were recorded every 10 s, Tb every minute. During the first 3 h post-treatment, modafinil and METH significantly and dose-dependently increased EEG wake time (P < .01 for 30 mg/kg modafinil, all other P < .0001) and wake episode duration. Although the cumulative increases in wakefulness were statistically equivalent, METH, but not modafinil, produced subsequent rebound hypersomnolence. At these equipotent wake-promoting doses, modafinil produced the same total amount of REM sleep inhibition but during a longer time than METH. Modafinil also increased LMA amount (counts/h, P < .001) and LMA intensity (counts/min awake, P < .001) less than METH. Both rebound hypersomnolence and increased LMA intensity, which are undesirable features in wake-promoting drugs, were not observed after modafinil treatment, and thus further differentiated modafinil from amphetamine-like stimulants.